Kritik Teologi Terhadap Pandangan Sekuler dalam Teori Belajar: Refleksi bagi Guru Kristen - Armela Nababan; Martina Labora Nainggolan; Yusniarti Situmorang; Hisardo Sitorus (Pusat riset dan Inovasi Nasional, 2025)
Modern education has produced various learning theories such as behaviorism, cognitivism, humanism, constructivism, and postmodernism, each contributing significantly to the understanding of learning processes, motivation, and knowledge formation. However, these theories are rooted in secular philosophical foundations that place humanity at the center of truth while neglecting the spiritual dimension revealed in Scripture. This condition creates tension for Christian education, which upholds the Bible as the epistemological basis and ultimate purpose of learning. This study aims to critically examine the secular assumptions embedded within modern learning theories, identify pedagogical elements that can be integrated into Christian education, and formulate strategies for Christian educators to utilize secular theories without compromising their theological foundation. The research employs a descriptive qualitative method through a literature review of books, journals, and relevant academic sources. The findings indicate that although modern learning theories offer valuable pedagogical insights, they contain naturalistic, rationalistic, humanistic, and relativistic assumptions that must be filtered through biblical theology. Christian educators are not required to reject secular theories entirely; rather, they bear an apologetic responsibility to discern useful methods, reject conflicting philosophical assumptions, and direct the entire learning process toward glorifying God. Thus, modern learning theories can function as effective tools within Christian education when positioned correctly as pedagogical instruments under the authority of Scripture.